Study of endostatin, tumstatin and PEDF, the natural angiogenesis inhibitors, potential in avasculargenic therapy - V. G. Likhvantseva; E. V. Arutyunyan; A. I. Miroshnikov; A. Yu. Salihov; O. V. Belous; K. D. Kurtshalidze; R. S. Esipov; K. A. Bejrahova; V. N. Stepanenko (Oftalʹmologiâ, 2014)
Purpose: To evaluate the potential of endostatin, tumstatin and PEDF in avasculargenic therapy.Methods: The avasculargenic potential of the natural angiogenesis inhibitors was explored on the model of alkaline burn, attended with angiogenesis of cornea. The model was developed on 8 rabbits. The injections were performed in calculated and tenfold increased dose after the vascularization had been formed. The injections were made daily, subconjunctively. There were 10 injections in total. The animals were observed for three months.Results: The clinical findings were obtained which prove the efficiency of the natural angiogenesis inhibitors in avasculargenic therapy. Tumstatin was registered as possessing the maximum clinically significant dose-dependent avasculargenic potential.Conclusion: The avasculargenic potential of the natural angiogenesis inhibitors — endostatin, tumstatin and PEDF — in avasculargenic therapy has been experimentally explored. As a result there was obtained the evidence of the clinically significant dosedependent avasculargenic potential of tumstatin, the natural angiogenesis inhibitor.